Review Design Struktur Pada Gedung B Universitas Tribhuwana Tunggadewi Malang - Sumarno, Andi; Wijaya, Handika Setya ; Suhudi (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2019)
The design review of the structure building is located in Lowokwaru sub-district, Malang Regency, East Java Province with an area of 4.78 hectares. So far, there has not been a review of design in Building B of the Tunggadewi tribhuwana university of Malang. Therefore, it is necessary to conduct research on a review of the structural design of building B. The structure design review aims to determine the strength of the previous building B for the addition of two floors in building B at the Tunggadewi Malang tribhuwana university. Design review is carried out with two structural designs, the first is a concrete structure design with dimensions of forty square centimeters, the second is a steel structure design with three hundred and fifty wf. The two structures are designed to determine the dimensions of the column beams when adding two floors to the structure. So as to produce dimensions in the beam column which will be used in the structure to be built in building B at the tribhuwana tunggadewi malang university